Improving Strengths of Porcelanite Aggregate Concrete by Adding Chopped Carbon Fibers - Hama, Sheelan M.; Hama, Shaho Mahmoud; Mhana, Mohammed H. (Al-Nahrain Journal for Engineering Sciences, 2018)
In this work chopped carbon fibers are used to improve tensile strength of Porcelanite lightweight aggregate concrete. Silica fume was added in order to improve the mixes compressive strength. Silica fume increase water demand and using fibers reduce workability, to improve workability and decrease water demand high rang super plasticizers are used. The results showed that compressive strength, splitting tensile strength, modulus of elasticity of carbon fibers Porcelanite lightweight aggregate concrete increase with increasing of carbon fiber up to 2% compared to reference Porcelanite lightweight aggregate concrete without fibers. The percentages of increasing were 14.40%, 68.00%, and 10.66% for compressive strength, splitting tensile strength, and modulus of elasticity, respectively.  Flexural Strength continues in increase with increase of fibers. The dry unite weight of mixes with chopped fiber decrease with increase of fiber percentage. Besides the chopped carbon improved the ductility of Porcelanite lightweight aggregate concrete and that clear from stress-strain relationship.